2019
DOI: 10.3126/jkmc.v8i2.28168
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and concern towards anesthesia among patients undergoing surgical procedure: A cross-sectional study at pre-anesthetic clinic of a Teaching Hospital

Abstract: Background: With the advent of anesthesia, surgery is no longer a race against the clock and surgeons. Many studies in the past have demonstrated limited knowledge among patients about various aspects of anesthesia.Objectives: To assess the awareness and concern of elective surgical patients towards anesthesia.Methodology: A cross-sectional questionnaire survey was conducted over two months’ period in adult patients of age eighteen years and above. Two hundred surgical patients accessing services at the pre-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
2
1
0
Order By: Relevance
“…As a result, pregnant women who have previously had operations or exposure to anesthesia were five times more likely to have good knowledge about anesthesia for CS than pregnant women who had no previous operations. This finding is consistent with studies conducted in Jimma University specialized hospital in Ethiopia [ 10 ], India [ 22 ], Pakistan [ 17 , 23 ] Turkey [ 24 ], and Nepal [ 25 ] which showed that patients with previous exposure to anesthesia or surgery had good knowledge of anesthesia techniques compared to those without previous exposure. This could be because pregnant women who have had previous operations or exposure to anesthesia may exert more effort to get accurate information about it, thereby raising their knowledge level towards anesthesia.…”
Section: Discussionsupporting
confidence: 91%
“…As a result, pregnant women who have previously had operations or exposure to anesthesia were five times more likely to have good knowledge about anesthesia for CS than pregnant women who had no previous operations. This finding is consistent with studies conducted in Jimma University specialized hospital in Ethiopia [ 10 ], India [ 22 ], Pakistan [ 17 , 23 ] Turkey [ 24 ], and Nepal [ 25 ] which showed that patients with previous exposure to anesthesia or surgery had good knowledge of anesthesia techniques compared to those without previous exposure. This could be because pregnant women who have had previous operations or exposure to anesthesia may exert more effort to get accurate information about it, thereby raising their knowledge level towards anesthesia.…”
Section: Discussionsupporting
confidence: 91%
“…Accordingly, pregnant women who have had previous operation or exposure to anesthesia were 5 times more likely to have good knowledge about anesthesia for CS as compared to pregnant women who hadn't any previous operation. This nding is consistent with studies conducted in Jimma University specialized Hospital Ethiopia (17), India (20), Pakistan (13,23) Turkey (24), and Nepal (25) which showed that patient with previous exposure of anesthesia or surgery had good knowledge of anesthesia techniques as compared to those without previous exposure. This might be due to that pregnant women who have had previous operation or exposure to anesthesia may spend more effort to get accurate information about it which improves their knowledge level towards anesthesia.…”
Section: Discussionsupporting
confidence: 91%
“…Obstetric anesthesia is differs from other anesthesia specializations because anesthetists deal with two lives and the consequences of pregnancy-induced alterations to all systems. 4,5 The use of regional anesthetic for cesarean section has increased, while that of general anesthetic has decreased. The rationale for this transition is that general anesthesia has several consequences that cause maternal morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%